2019
DOI: 10.22271/tpr.2019.v6.i1.013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of soil microbial population under different land use

Abstract: Soil microorganism is important for the restoration, sustainability, balancing of soil ecosystem and organic matter transfer. The diversity of the microbial community in soil is closely related to the functions and structure of its surrounding ecosystem. The aim of this research work is principally on the identification of microbial population under different land use types in Akure, Nigeria. The land use types were oil palm, teak plantation, unclear forest, and cassava and sugar plantations. The soil samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…These results seem to indicate a relatively low capacity of the soils to sustain higher microbial populations above 10 5 CFU/g of soil. Similar observations were made by Akande and Adekayode (2019) while comparing the levels of microbial populations isolated from different types of soils.…”
Section: Discussionsupporting
confidence: 79%
“…These results seem to indicate a relatively low capacity of the soils to sustain higher microbial populations above 10 5 CFU/g of soil. Similar observations were made by Akande and Adekayode (2019) while comparing the levels of microbial populations isolated from different types of soils.…”
Section: Discussionsupporting
confidence: 79%
“…These results imply that the microbial populations in the studied soils are quite low, indicating that the soils may have a limited ability to sustain populations of microorganisms exceeding 10 5 CFU/g of soil [4]. Similar findings were reported by Akande and Adekayode (2019) in a study that compared microbial populations across different soil types and also found the microbial populations in soils are relatively low [23]. This result indicated the low microbial populations observed in these soils might be attributed to suboptimal soil conditions such as pH, nutrient availability, temperature, and moisture content [24].…”
Section: A Microbial Population In Plastic Contamination Sitessupporting
confidence: 89%
“…The microbial population in soil was determined using the dilution spread plate technique as described in previous studies (Kakosová et al, 2017;Akande and Adekayode, 2019;Kumar et al, 2021). For bacteria and fungi, Nutrient Agar (NA) and Potato Dextrose agar (PDA) were the preferred growth media.…”
Section: Microbial Populationmentioning
confidence: 99%